Corruption in Nepal: Investigating the gap between media portrayal and actual evidence - Khanal, Shreedhar (A Bi-annual South Asian Journal of Research & Innovation, 2025)
This study aims to analyze the corruption in Nepal from the perspective of media Portrayal against the Actual Evidences in the empirical context. Ideally, the media are supposed to act as a watchdog and expose wrongdoings in addition to awaking the citizens. However, this paper indicates a critical gap between what has been reported in the news and the findings of corruption navigating the analysis of the content published in two popular newspapers in Nepal, i.e. Gorakhapatra and Kantipur take the methodological cut-off point between 2065 mansir (November-December, 2007) and 2081 Mansir (November-December, 2024). Based on media coverage and governmental publications, Nepali journalism seems to be under political and financial pressure. The constraints also restrict the ability of journalists to fairly investigate and report on such matters and hence biased, partial or incomplete reporting. These misrepresentations hide the real magnitude of corruption and undermine the consciousness of the masses. The results indicate that the media has not only been unsuccessful in its democratic obligation, but also in living up to its democratic ideals. The remedy to these weaknesses would be to ensure more press freedom, independence against unnecessary interference, and enhanced investigative journalism.